Lingual frenotomy in univiteline twin babies: case report (Research, Society and Development, 2020)
Ankyloglossia is an anatomical variation that has been associated with a variety of problems such as: suckling, swallowing and speaking. In this perspective, frenotomy is a surgical procedure commonly performed on babies to correct ankyloglossia. In this sense, the objective of this work is to report a clinical case of ankyloglossia in which the frenotomy procedure was performed on twin newborns, who had difficulty breastfeeding, carried out in the Extension Project “Língua Solta”, from the Federal University of Pernambuco. The evaluation of the lingual frenulum followed the protocol recommended by Martinelli, 2013. After application of the protocol, newborns showed the need to perform frenotomies. The surgeries were performed and, after 7 days, the babies showed significant improvement in breastfeeding. The diagnosis made, through the protocol and experienced professionals, is of fundamental importance for the success of the surgery. In addition, early intervention contributes to improved breastfeeding and development of the newborn.